Drunkorexia: An Examination of the Role of Theory of Mind and Emotional Awareness among Adolescents. Issue 1 (2nd January 2021) - Laghi, Fiorenzo; Pompili, Sara; Bianchi, Dora; Lonigro, Antonia; Baiocco, Roberto
ABSTRACT: This study aimed to investigate Theory of Mind (ToM) and emotional awareness in drunkorexia, an emerging behavior characterized by calorie restriction when drinking alcohol is planned. A sample of 246 adolescents (148 females, 98 males; range 17–20) completed self-reported measures assessing drunkorexia, ToM and lack of emotional awareness. Drunkorexia was negatively correlated with ToM abilities, with reading neutral emotions, and positively with lack of emotional awareness. ToM and lack of emotional awareness were also found to predict drunkorexia. Findings highlighted that adolescents who engage in drunkorexia may have difficulties in reading others' mental states and being aware of their emotions.